2012
DOI: 10.4321/s1130-01082012000100004
|View full text |Cite
|
Sign up to set email alerts
|

Effect upon hospital activity of the application of a continued care model centered on patients with inflammatory bowel disease

Abstract: Background: since 1999, the Crohn-Colitis Care Unit (UACC) has been dedicated to the integral management of patients with Crohn's disease (CD) and ulcerative colitis (UC). The working methodology of the UACC is based on personalized, continued, nonphysical presence, open access and patient-centered care. From its creation, the UACC has experienced an increase in the number of its users and outpatient services. However, the impact of the activity of the UACC upon patient hospitalization is not known.Objectives:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…A recent multicenter, randomized controlled trial including more than 900 patients with different subtypes of IBD showed that compared with standard care, empowerment through these systems reduces outpatient visits and hospital admissions, with potential cost savings [8]. Web-based systems are currently the most useful platforms, and their application allows development of distance care projects aimed at providing access to health care in remote areas [23,24]. These models promote collaboration and knowledge exchange between specialists, potentially reducing variability in clinical practice, and could modify the future structure of health systems if they prove to be cost-effective.…”
Section: Introductionmentioning
confidence: 99%
“…A recent multicenter, randomized controlled trial including more than 900 patients with different subtypes of IBD showed that compared with standard care, empowerment through these systems reduces outpatient visits and hospital admissions, with potential cost savings [8]. Web-based systems are currently the most useful platforms, and their application allows development of distance care projects aimed at providing access to health care in remote areas [23,24]. These models promote collaboration and knowledge exchange between specialists, potentially reducing variability in clinical practice, and could modify the future structure of health systems if they prove to be cost-effective.…”
Section: Introductionmentioning
confidence: 99%
“…Generating scientific knowledge about the life experiences and social support of those affected by Crohn's disease can help health professionals adopt a more holistic approach to their work with these patients, taking into account patient subjectivity and their perceptions about the problem . Particularly in Spain, several studies have shown the interest of this kind of proposals towards care improvement from a holistic perspective, focusing on implementing specialised units for those affected by CD . Few studies have focused on the life experiences and coping abilities from the perspective of those who have an inflammatory bowel disease (IBD).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in Spain, several studies have shown the interest of this kind of proposals towards care improvement from a holistic perspective, focusing on implementing specialised units for those affected by CD (14,15). Few studies have focused on the life experiences and coping abilities from the perspective of those who have an inflammatory bowel disease (IBD).…”
Section: Introductionmentioning
confidence: 99%
“…For example in Spain the Crohn colitis care unit (UACC), a care program using a remote communication system, proved its efficacy by demonstrating a decrease in the ratio of hospitalized/UACC-registered patients between the start and end of a study period. 90 The aim of these remote-care applications is to improve medical adherence and QoL of patients with IBD, which must be higher than with a standard clinical follow up. This is achieved through a better understanding of the disease by the patient, and better communication between patients and healthcare providers.…”
Section: Telemedicine In Ibdmentioning
confidence: 99%